Design and Analysis of Hybrid Solar Vehicle (International Journal of Engineering and Computer Science, 2017)
Conventional combustion engine vehicles are very much responsible for various kinds of pollutions in current decade due to emission of Green-house gases. To control the problem of pollution occur by Combustion engines and also reduce the effect of Global warming, renewable energy sources are come in picture. Various kind of renewable energy sources are used for domestic as well as industrial applications. In Asian Countries Solar energy is accomplished in very large amount. To overcome the disadvantages of Conventional combustion engine vehicles this research introduced Hybrid Solar Vehicle.Hybrid Solar Vehicle is performs on the principle of Photovoltaic Solar Cells. Sunlight or Solar energy is directly converted into Electrical energy by using Photovoltaic cells for displacement of vehicle. Lithium-ion batteries are used in this future designed Hybrid vehicle for storing the Electric Power which is generated from Photovoltaic Cells. This future designed vehicle is more efficient in the manner of Green-house gases emission.